Teknik Komunikasi Persuasif Ustadz Syamsuddin Nur pada Akun Tiktok @syam_elmarusy - Sopiah, Devi Ulfah; Sumijaty, Siti; Sukayat, Tata (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This article aims to find out how to use persuasive communication techniques on the TikTok account @syam_elmarusy using five methods, namely Association, Integration, Pay off and Fear Arousing, Icing, Red Hearing techniques. The research method used is a descriptive method with a qualitative approach. Researchers analyzed 15 video content which contained persuasive communication techniques in it. The results of this research show that of the 15 video contents, there are 3 videos with the Association Technique, 3 videos with the Integration Technique, 3 videos with the Pay off and Fear Arousing Method, 3 videos with the Icing Method, 3 videos with the Red Hearing Method.